+0  
 
0
192
1
avatar

How to Convert these two functions?

 

Guest Dec 7, 2017

Best Answer 

 #1
avatar+7177 
+1
1.      f(x)  =  2(x - 1)

        

Using the rule   \(\frac{x^a}{x^b}=x^{a-b}\)  , we have
  f(x)  =  \(\frac{2^x}{2^1}\)

 

 

 
  f(x)  =  \(\frac{2^x}{2}\)

 

 
  f(x)  =  \(\frac12\cdot2^x\)

 

 

Here,   a = 1/2   and   b = 2  .
   

 

 

 
2. f(x)  =  2(3x + 4)

 

Using the rule   xa · xb  =  x(a + b)  , we have
  f(x)  =  23x · 24

 

 

 
  f(x)  =  23x · 16

 

Using the rule   (xa)b  =  xab  , we have
  f(x)  =  (23)x · 16

 

 

 
  f(x)  =  16 · 8x   Here,   a = 16   and   b = 8  .
hectictar  Dec 7, 2017
 #1
avatar+7177 
+1
Best Answer
1.      f(x)  =  2(x - 1)

        

Using the rule   \(\frac{x^a}{x^b}=x^{a-b}\)  , we have
  f(x)  =  \(\frac{2^x}{2^1}\)

 

 

 
  f(x)  =  \(\frac{2^x}{2}\)

 

 
  f(x)  =  \(\frac12\cdot2^x\)

 

 

Here,   a = 1/2   and   b = 2  .
   

 

 

 
2. f(x)  =  2(3x + 4)

 

Using the rule   xa · xb  =  x(a + b)  , we have
  f(x)  =  23x · 24

 

 

 
  f(x)  =  23x · 16

 

Using the rule   (xa)b  =  xab  , we have
  f(x)  =  (23)x · 16

 

 

 
  f(x)  =  16 · 8x   Here,   a = 16   and   b = 8  .
hectictar  Dec 7, 2017

5 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.